Purging of Miners in Almadén and Arrayanes in 1939 - Hernández Sobrino, Ángel; Almansa Rodríguez, Emiliano (Hispania Nova, 2024)
Workers at the Almadén mercury mine (Ciudad Real) and the Arrayanes lead mine in Linares (Jaén) underwent a purging process at the end of the civil war. At that time, both mines were governed by the same Board of Directors, dependent on the Ministry of Finance, and at the end of the conflict two purification commissions were appointed, one for Almadén and the other for Arrayanes, establishing three levels of misconduct: minor, less serious, and serious. At Almadén, 54% of the 2,550 workers suffered some kind of sanction, while at Arrayanes, which employed 640 workers, the percentage of sanctioned workers rose to 76%. In the post-war period, the Council handled the situation of the expelled workers as it pleased, for while at Almadén it readmitted 72 expelled workers to increase mercury production, no effort was made at Arrayanes because the lead mine was loss-making.